2006
DOI: 10.2466/pms.103.1.145-150
|View full text |Cite
|
Sign up to set email alerts
|

Development of Eating Behavior by Japanese Toddlers in a Nursery School: Relation to Independent Walking

Abstract: The eating behavior of 32 toddlers in a nursery school at 10, 12, and 14 months old was observed in relation to the age at onset of independent walking. With increasing age, the frequency at which the toddlers ate food given by a teacher decreased, and the frequency at which the toddlers ate by themselves increased. The toddlers who started walking earlier also advanced faster in the development of eating behavior. The time when the frequency of eating by oneself surpassed the frequency of passive eating coinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In recent years, several studies have begun to shed light on the issue. For example, Koda et al (2006) observed the eating behavior of 32 toddlers from 10 to 14 months of age in a nursery school in Japan. They found that as children grew older, the rate at which they ate by themselves using tools increased.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have begun to shed light on the issue. For example, Koda et al (2006) observed the eating behavior of 32 toddlers from 10 to 14 months of age in a nursery school in Japan. They found that as children grew older, the rate at which they ate by themselves using tools increased.…”
Section: Introductionmentioning
confidence: 99%